2015
DOI: 10.1002/mus.24654
|View full text |Cite
|
Sign up to set email alerts
|

Motion control of the rabbit ankle joint with a flat interface nerve electrode

Abstract: INTRODUCTION A flat interface nerve electrode (FINE) has been shown to improve fascicular and subfascicular selectivity. A recently developed novel control algorithm for FINE was applied to motion control of the rabbit ankle. METHODS A 14-contact FINE was placed on the rabbit sciatic nerve (n=8), and ankle joint motion was controlled for sinusoidal trajectories and filtered random trajectories. To this end, a real time controller was implemented with a multiple-channel current stimulus isolator. RESULTS Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 24 publications
(29 reference statements)
0
3
0
Order By: Relevance
“…The amplitude of the action potentials detected by extraneural interfaces is much lower than in the case of intraneural interfaces and depends on the distance of the electrodes from the active axons [12]. Extraneural interfaces have been widely applied in acute studies of motor behavior, for recording and stimulation of peripheral nerves of cats [38,39,41,42], rabbits [9,43,44], dogs [45,46], rodents [47], human models [48], and human subjects [49][50][51][52][53][54]. Previous work [55] on the development and implementation of FINE has achieved many breakthroughs, including (i) a high degree of selectivity, as estimated by indi vidual fascicle recording; (ii) use of blind source algorithms to decode motor commands; and (iii) (by employing arrays of interfaces along the peripheral nerve) excitation of fibers hav ing small diameters before large fibers, thereby reversing the usual recruitment order.…”
Section: Extra-neural Interfacesmentioning
confidence: 99%
“…The amplitude of the action potentials detected by extraneural interfaces is much lower than in the case of intraneural interfaces and depends on the distance of the electrodes from the active axons [12]. Extraneural interfaces have been widely applied in acute studies of motor behavior, for recording and stimulation of peripheral nerves of cats [38,39,41,42], rabbits [9,43,44], dogs [45,46], rodents [47], human models [48], and human subjects [49][50][51][52][53][54]. Previous work [55] on the development and implementation of FINE has achieved many breakthroughs, including (i) a high degree of selectivity, as estimated by indi vidual fascicle recording; (ii) use of blind source algorithms to decode motor commands; and (iii) (by employing arrays of interfaces along the peripheral nerve) excitation of fibers hav ing small diameters before large fibers, thereby reversing the usual recruitment order.…”
Section: Extra-neural Interfacesmentioning
confidence: 99%
“…Reconstruction of fast motion by peripheral nerve stimulation was reported by H.J. Park et al [ 30 ], but their study used a large power source and a wired connection between the power source and the nerve. Hence, the proposed method will contribute to reconstructing functional motion for patients with peripheral nerve injury or disorder using a wirelessly powered implantable device.…”
Section: Discussionmentioning
confidence: 99%
“…FINE can be designed in a multi-channel configuration and, moreover, compresses and reshapes the nerve into a flatter conformation, thereby allowing the central fascicles to be closer to the surface and providing more selective axonal population activation (Fig. 3) [63,66,105,151,161]. Additionally, intraoperative studies in the human femoral nerve showed that muscles innervated by the femoral nerve could be independently and selectively stimulated with a FINE device [133].…”
Section: Flat Interface Nerve Electrodesmentioning
confidence: 99%